The Influence of Profitability, Liquidity, and Leverage on Financial Distress of Tourism Sector Companies - Amalina Nur Izzah; Mariana Mariana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of profitability, liquidity, and leverage on financial distress of tourism sector companies listed on the Indonesia Stock Exchange for the period 2018-2023. The number of companies used as samples was 32 companies with certain criteria. The sampling technique used purposive sampling, so that the total analysis units in this study were 192. Multiple linear regression analysis was used in the analysis of this research data. The results of the study indicate that profitability, liquidity, and leverage have a positive effect on financial distress. Thus, it can be concluded that the overall results of this study are that profitability, liquidity, and leverage can influence financial distress.